The use of the strategy of convergence of diaspora and its impact on the geometric thinking of the students of the second intermediate grade in mathematics (Journal of the College of Basic Education, 2022)
The current research aims to identify (the use of the strategy of convergence of fragments in the geometric thinking of the students of the second intermediate grade in mathematics). For the purpose of verifying the aim of the research, the following zero hypothesis was formulated: “There is no statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who study according to the strategy of diaspora familiarity and the average scores of the control group students who study according to the usual method in the test Geometric thinking in mathematics.